2015
DOI: 10.1186/s12986-015-0035-0
|View full text |Cite
|
Sign up to set email alerts
|

Low-calcium diet prevents fructose-induced hyperinsulinemia and ameliorates the response to glucose load in rats

Abstract: BackgroundConsuming a fructose-rich diet leads to hyperinsulinemia, impaired glucose tolerance, and insulin resistance. In humans, the consumption of high levels of refined sugars often coincides with a diet containing suboptimal levels of calcium. Calcium and carbohydrate metabolism interact, so there is potential for fructose to have different health outcomes depending on whether the diet is calcium-rich or calcium-poor.MethodsWe evaluated the metabolic effects of feeding fructose to rats that were maintaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Lower levels of circulating IGF-1 is known to be associated with reduced PCa tumor cell growth, while higher level of insulin and IGFBP-1 and −2 are related to increased PCa cell proliferation. Experimental studies have shown the associations between refined carbohydrate intake and hyperinsulinemia (33). Epidemiologic studies also support the positive association between high refined carbohydrate diet and insulin resistance (34)(35)(36).…”
Section: Discussionmentioning
confidence: 87%
“…Lower levels of circulating IGF-1 is known to be associated with reduced PCa tumor cell growth, while higher level of insulin and IGFBP-1 and −2 are related to increased PCa cell proliferation. Experimental studies have shown the associations between refined carbohydrate intake and hyperinsulinemia (33). Epidemiologic studies also support the positive association between high refined carbohydrate diet and insulin resistance (34)(35)(36).…”
Section: Discussionmentioning
confidence: 87%
“…Thus it is unlikely that changes in glucose metabolism or insulin sensitivity accounted for the observed differences in serum lipids of the rats. Rats fed very low Ca (0.75Ca) had lower serum insulin compared to the other groups that may be explained by impaired secretion of insulin from pancreatic β-cells [66].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the increase in the use of refined food, which is rich fructose, has raised concerns about the potential adverse on public health. The metabolic pathway of fructose is associated with hepatic gluconeogenesis and lipid biogenesis . The main organ in metabolism, the liver transports energy to other cells in the form of glucose, lactate and lipids.…”
Section: Introductionmentioning
confidence: 99%
“…The metabolic pathway of fructose is associated with hepatic gluconeogenesis and lipid biogenesis. [8] The main organ in metabolism, the liver transports energy to other cells in the form of glucose, lactate and lipids. A large amount of fructose metabolism is in the liver.…”
Section: Introductionmentioning
confidence: 99%